(Im)mobile phones: “Stuckness” and mobile phones in a neighbourhood in a small town in South Africa (Communicare: Journal for Communication Studies in Africa, 2022)
This qualitative study examines the role of the mobile phone in negotiating the day-to-dayexperience of social immobility for young users in a low-income area in a small town in SouthAfrica. What does the mobile phone become when one is not part of a mobile globalised elite,but poor, unemployed and living on the margins of society in the global south? While researchon mobile phones in developed countries suggest these devices facilitate the creation of asociety free from the confines of local geography and community, where the user can craft anindividualised networked sociability, this may not be the reality in the global south. In our study,mobile phones were seen to amplify a communal sociability where privacy is largely absent fromthe densely contiguous neighbourhood where life happens on the streets for all to see. Thisstudy demonstrates how, in a particular context, mobile phones and the mobile Internet do notnecessarily facilitate a mobile world where individual networks allow an escape from local normsand structures, but may instead facilitate communal networks that bind users to the local and theco-present and so facilitate “stuckness”, a term we use to reflect social immobility and the inabilityto escape the disciplinary surveillance of the co-present.